LITERASI METODE PENELITIAN DAN BISNIS TEKNOLOGI KREATIF DI ERA NEW NORMAL - Roymon Panjaitan; Myra Andriana; Tantik Sumarlin; Sindhu Rakasiswi; Yuli Fitrianto (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
The Covid-19 pandemic that hit the world including Indonesia had an impact on all aspects, one of which was the economic aspect. MSMEs are the most affected, where 50% of MSMEs are forced to go out of business because economic activities are stopped suddenly, and demand decreases. MSME turnover has dropped dramatically by around 40%-70%. Business people, especially MSMEs, have to start adapting to the new normal to maintain their business. At this webinar, various solutions will be given to the confusion of the community, especially MSME entrepreneurs, where they can choose the tips and solutions offered that are suitable to be applied according to their fields to survive and even grow during a pandemic, starting from business opportunities, to tips and tricks for using the right technology that can support MSME programs. The material in this webinar was delivered by 5 resource persons who are experts in their fields. The implenetation of this activity is carried out through the Zoom application and Live Youtube, with a total of 514 participants from various professions and MSME players. Webinar participants are given the opportunity to conduct questions and answer after all the resource persons have delivered their material. Participant who attend and fill in attendance receive certificates and material that are presented in this webinar.